1996
DOI: 10.1088/0268-1242/11/11s/008
|View full text |Cite
|
Sign up to set email alerts
|

A possible road to 77 K single-electron devices

Abstract: The application of single-electron devices is restricted to temperatures at which Coulomb blockade occurs. The most critical parameter of the devices is the tunnelling capacitance. Operation at liquid helium temperature, for example, requires tunnelling capacitances of the order of 20 aF. To realize such low capacitances, advanced electron-beam lithography below 20 nm is mandatory in fabrication schemes proposed up to now. Here we will present a new fabrication process that is capable of tunnelling capacitance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…To shine more light on the origin of these thermally induced irregularities in the staircase, transport measurements were performed over a larger temperature range. The grey scale plot in figure 7 illustrates the temperature dependence of the differential conductance dJ /dU between 4 K and 200 K. No change in the I/V characteristic could be detected for this contact after it was cooled back again to 4 K. At about 80 K, the steps are starting to smear out but can still be recognized up to 150 K. The maximal temperature T max for Coulomb blockade effects to be observable can be estimated from [37] T max ≈ e 2 /8k B C which leads in the present case (total capacitance C = C 1 + C 2 = 1.3 × 10 −18 F) to a predicted temperature limit of 179 K. From the fact that this value is in fair agreement with the observed vanishing of the steps at about 150 K, it can be concluded that thermally induced charge fluctuations, not structural instabilities or competing transport processes, are the main source for the changes in figure 7.…”
Section: I/v Curves With Regular Current Steps: Coulomb Staircasesmentioning
confidence: 99%
“…To shine more light on the origin of these thermally induced irregularities in the staircase, transport measurements were performed over a larger temperature range. The grey scale plot in figure 7 illustrates the temperature dependence of the differential conductance dJ /dU between 4 K and 200 K. No change in the I/V characteristic could be detected for this contact after it was cooled back again to 4 K. At about 80 K, the steps are starting to smear out but can still be recognized up to 150 K. The maximal temperature T max for Coulomb blockade effects to be observable can be estimated from [37] T max ≈ e 2 /8k B C which leads in the present case (total capacitance C = C 1 + C 2 = 1.3 × 10 −18 F) to a predicted temperature limit of 179 K. From the fact that this value is in fair agreement with the observed vanishing of the steps at about 150 K, it can be concluded that thermally induced charge fluctuations, not structural instabilities or competing transport processes, are the main source for the changes in figure 7.…”
Section: I/v Curves With Regular Current Steps: Coulomb Staircasesmentioning
confidence: 99%